For a competitive edge in services, invest in the right people and processes - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Great products alone will not give rise to transformative customer experiences. Businesses that have carved out a competitive edge in services also know that it requires far more than frontline skills and knowledge to succeed with customers in the longer term. But how and where should organisations be placing their focus to entrench customer service for strategic advantage? - a question that academics and industry practitioners attempted to answer at the Institute of Service Excellence at SMU Global Conference on Service Excellence 2011.